(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Marketing innovation is essential for the development of small and medium businessescreate a competitive advantage. Generate more income and if added value and innovation in the product will add even more added value.Marketing innovations play a new and increasing role in being able to interpret big data and use it to develop marketing strategies and products. Theory in this paper are marketing mix theory and entrepreneurship theory. Moreover, the literature reviews focus on marketing innovation variable, consumer buying behavior variable and competitive advantage variable in to. Al least, marketing innovation is important tool that entrepreneurs need to focus on. Marketing innovations include creating a variety of products personal value creation adding value targeting niche groups including the development of modern communication through new social media.